Attraction and retention of Generation Y employees in PricewaterhouseCoopers / Nur Insyirah Abdul Manan and Nur Aimi Aziz - Abdul Manan, Nur Insyirah; Aziz, Nur Aimi (Faculty of Business and Management, 2013)
Attraction and Retention of Generation Y employee is one of the famous issues faced by organization nowadays. Organization need to be able to attract and retain its employee in order to gain competitive advantage. As for PricewaterhouseCoopers, Kuala Lumpur, researcher is attracted to identify what are the determinants of employee attraction and retention in the organization. This is because based on the observation made by researcher, most of the employees will remain in PricewaterhouseCoopers if they find that the offered made by the organization are attractive for them. The first research objective is to identify if there is any relationship between compensation package and attraction and retention of Generation Y employees. Second objective is to identify if there is any relationship between growth opportunities and attraction and retention of Generation Y employees. Last but not least, the third objective is to identify if there is any relationship between good management and attraction and retention of Generation Y employees. The total number of respondent’s is 150 people selected from Human Capital Department through Stratified Sampling method. The data were collected through distribution of questionnaire survey and interpreted into readable and informative data through Reliability Analysis, Descriptive Analysis and Pearson’s Correlation. The findings supported all three (3) objectives which mean there is relationship between all three (3) independent variables which are compensation package, growth opportunities and good management with the dependent variable, attraction and retention of Generation Y employees in PricewaterhouseCoopers.